THU0066 Phenotypical and Functional Characteristics of in Vitro Expanded Adipose-Derived Mesenchymal Stem Cells from Patients with Systemic Sclerosis. (23rd January 2014) - Capelli, C.; Caviggioli, F.; Sambataro, D.; Zaccara, E.; Vinci, V.; Maglione, W.; Klinger, M.; Introna, M.; Polosa, R.; Del Papa, N.
Abstract : Background: Adult stem cells, expecially those of mesodermal origin (MSCs), have received attention as an ideal source of regenerative capable cells because of their multipotentially and ability to replicate. Regenerative cells from the bone marrow, peripheral blood, and umbilical cord blood have been used to treat a variety of diseases. Adipose tissue is an attractive source of adult stem cells due to its abundance and surgical accessibility. Recent studies have shown the efficacy of the autologous fat grafting in the treatment of different skin diseases including localized scleroderma and ischemic diseases. Objectives: We characterized phenotypically and functionally adipose tissue-derived mesenchymal stem cells (ADMSCs) from patients with Systemic Sclerosis (SSc). Methods: Human adipose tissue samples were obtained from 10 patients with the diffuse form of SSc (dcSSc) undergoing autologous lipostructure for the treatment of fibrotic perioral changes. As controls, adipose tissue samples were obtained from 10 healthy donors (HD) undergoing aesthetic surgery. Lipoaspirate tissue was collected from elective liposuction procedures and processed by both explant and enzymatic methods. Key parameters of ADMSCs function and phenotype were assessed including the ability to: express cell surface antigens defining the MSC population (CD105, CD73, CD29, CD90, CD44 marker profile was examined by FACS analysis), proliferate (growth kinetics assay), differentiate along the adipogenic and osteogenic lineages, suppress in vitro lymphocyte proliferation induced by the mixed lymphocyte reaction. Results: Cultured ADMSCs obtained from the processing of adipose tissue showed no significant differences in morphology and in proliferation rate in the culture conditions used. Phenotypically, SSc ADMSCs highly expressed CD105, CD73, CD90, HLA-ABC and were mostly negative for HLA-DR expression. The absence of contaminating hematopoietic stem cells was confirmed by the negative expression of CD34, CD14 and CD45 antigens in all studied cases. No phenotypic differences were observed between ADMSCs from patients with SSc and controls. When cultured in standard induction medium, all SSc and HD ADMSCs differentiated toward the osteogenic and adipogenic lineages. In MLR assays, no significant differences in ADMSCs mediated inhibition of proliferation were observed between SSc patients and controls. Conclusions: Autologous adipose graft could be a new therapeutic option for the treatment of skin diseases such as SSc. The mechanisms through which adipose tissue exerts its therapeutic potential in tissue repair is not yet fully defined, but it might be related to the well known ability of MSCs to modulate inflammatory and autoimmune process, secrete soluble factors capable to stimulate functional recovery of injured cells and differentiate into other cell types. The results of our study show that ADMSCs from patients with SSc exhibit the same phenotypic, proliferative, differentiation potential and immunosoppressive properties as HD. Further studies are need to clarify the ADMSCs specific contribution to the clinically relevant benefits in SSc soft-tissue reconstruction. Disclosure of Interest: None Declared